An isolated ulcerated forehead lesion in a 70‐year‐old man. (18th May 2017) - Cunningham, F.; Darling, M. I.; Gangopadhyay, M.; Jackson, R.; McKay, P.; Bilsland, D.
Abstract : Clickhere for the corresponding questions to this CME article.